The taboos of menarche: An approach to the experience of young chilean students - Fernández Olguín, Daniela (Revista de Psicología, 2012)
Even though menarche has been described as relevant to women’s subjectivity, it hasn’t had enough relevance among research and developments in the subject currently. This research attempts to describe and analyze the processes under which taboos work in the experience of menarche in a selection of young chilean females, within a time frame prior and posterior to their menarche. A qualitative methodology of case analysis is used, and the information is gathered with a semistructured interview. It is exposed that the taboos work in different dimensions for young women: family, their body and the bonds built with different others.